Bauran Pemasaran Pada Usaha Cake Dan Bakery “Hari-Hari” Di Kota Manado - Tobing, Ica Maria; Pangemanan, Paulus Adrian; Lolowang, Tommy Fredy (Sam Ratulangi University, 2024)
This research aims to describe the marketing mix at the Cake and Bakery